Mid Term Appraisal of the Tenth Five Year Plan (2002-03) to (2004-05) Government of Himachal Pradesh - Planning Commission (Planning Commission, 2002)
During the 1991-2001 decade the workforce increased from 22.14 lakh in 1991 to 29.92 lakh in 2001 recording a growth rate of 35.14% as against 17.54% growth in population over the same period. In the year 1991, the workforce constituted 42.82% of the total population while in 2001 it accounted for 49.23% In the year 1991, main workers constituted 34.40% of the total population while in 2001 they accounted for 32.31%. The marginal workers and non-workers constituted for 8.41% and 57.16%, respectively of the total population in 1991 while they accounted for 16.93% and 50.76%, respectively of the total population in 2001. There is a considerable increase in the workforce of marginal workers.
Planning Department, Government of Himachal Pradesh